Immune correlates of protection as a game changer in tuberculosis vaccine development - Jing Wang; Xiao-Yong Fan; Zhidong Hu (npj Vaccines)
Abstract The absence of validated correlates of protection (CoPs) hampers the rational design and clinical development of new tuberculosis vaccines. In this review, we provide an overview of the potential CoPs in tuberculosis vaccine research. Major hindrances and potential opportunities are then discussed. Based on recent progress, it is reasonable to anticipate that success in the ongoing efforts to identify CoPs would be a game-changer in tuberculosis vaccine development.